Anaplastic Thyroid Carcinoma, a Cytologic Perspective. Issue 5 (September 2015) - Goicochea, Lindsay; Staats, Paul N.
<x xml:space="preserve">Abstract</x> Abstract Anaplastic, or undifferentiated, thyroid carcinoma (ATC) is a highly aggressive disease with less than 1-year survival in nearly all patients with this disease. Because of its aggressive nature, ATC is frequently unresectable. Rapid and accurate pretreatment diagnosis is required to attempt local-regional control. Fine-needle aspiration (FNA) and core-needle biopsy (CNB) are the most widely used initial means of obtaining a tissue diagnosis of this entity, and these specimens are often the only tissue procured before definitive therapy. Although the literature on cytologic diagnosis of ATC is limited, the performance characteristics of FNA appear to be good, with high sensitivity and specificity. However, diagnosis can be challenging because of the variable appearance of aspirated cells of ATC and a broad differential diagnosis that includes medullary carcinoma, poorly differentiated thyroid carcinoma, lymphoma, primary thyroid sarcoma, and metastatic tumors. The use of a limited panel of immunohistochemical stains is often helpful in distinguishing these entities. Although ATC arises in many cases from a well-differentiated thyroid carcinoma, the limited nature of an FNA or CNB specimen usually precludes identification of an associated lower-grade lesion. Herein, we report a case of ATC diagnosed on FNA and CNB and review the diagnosis of ATC from a cytopathology perspective.